The effects of message framing on US police chiefs’ support for interventions for opioid use disorder: a randomized survey experiment - Brandon del Pozo; Saba Rouhani; Amelia Bailey; M. H. Clark; Kaitlin F. Martins; Fatema Z. Ahmed; Danielle Atkins; Barbara Andraka-Christou (Health & Justice)
Abstract Background US chiefs of police hold significant influence over the perceived acceptability and appropriateness of interventions for opioid use disorder (OUD) among the public, elected officials, and subordinate officers. This study assessed whether police chiefs’ support for such interventions was sensitive to framing an intervention’s benefits in terms that emphasize public health and harm reduction outcomes, versus terms typically indicative of public safety outcomes. Methods A two-armed survey utilizing a randomized, between-subjects design tested framing-based variance in support among US chiefs of police for overdose prevention centers, syringe service programs (SSPs), Good Samaritan laws, police naloxone distribution, trustworthiness of officers in recovery from OUD, and related propositions. Of 1,200 invitations, 276 chiefs participated (23%). The two experimental arms (n = 133, n = 143) were demographically balanced between both each other and non-respondents. Results Chiefs were more likely to agree that their mission was protecting public safety than protecting public health, even when both were defined using public health outcomes. Chiefs expressed significantly greater support for “overdose prevention sites” than “safe injection sites” (p = .018), low levels of support for SSPs regardless of framing (18% safety; 19% health), and comparably more support for Good Samaritan laws based on framing (62% safety vs. 54% health). Respondents voiced low levels of trust in officers recovering from OUD generally (31%), and significantly lower levels of trust when recovery involved the medication buprenorphine (10%; p < .001). Senior chiefs were significantly more likely to support SSPs (aOR 1.05; CI 1.01, 1.09) and overdose prevention sites (aOR 2.45; CI 1.13, 5.28) than less senior chiefs. Conclusions In this cross-sectional survey experiment, support for some interventions for OUD was greater among US chiefs of police when framed to emphasize positive public safety outcomes. Research is required to better understand low support for SSPs, mistrust of officers in recovery for OUD, and greater support for OUD interventions among senior chiefs.